The Politeness Comments on The Indonesian President Jokowi Instagram Official Account Viewed From Politico Pragmatics and The Character Education Orientation in The Disruption Era - Harun Joko Prayitno; Hari Kusmanto; Yakub Nasucha; Laili Etika Rahmawati; Norliza Jamaluddin; Samsuddin Samsuddin; Awla Akbar Ilma (Universitas Muhammadiyah Surakarta, 2019)
Politeness of expression and character education are both crucial aspects, in the current era of disruption, especially concerning sociopragmatic political purposes. The realization of politeness acts of language in the context of communication and global communication has now penetrated without limits on social distance, time, and goals. The problem is the act of language in electronic media, especially Instagram, giving space to the user to be more open in expressing his goals and objectives, including to the president in relation to specific goals and politics. This study aims to identify the forms of positive politeness acts of followers' comments on President Jokowi's official Instagram account and describe the intent of politico pragmatic power of positive politeness of followers of Jokowi's Instagram accounts. The data source of this study was the speech of followers on the official Instagram account of Indonesian President Jokowi #MenujuIndonesiaMaju managed by the President's Digital Communication Team for the period October-November 2018. The study data were in the form of comments from Jokowi's Instagram account followers who had positive politico pragmatic politeness. The data collection technique was carried out using documentation, note-taking techniques, and continued with heuristic listening techniques. Data analysis was performed with an intralingual equivalent technique which was strengthened by an extra lingual equivalent and sharpened with Levinson's politeness analysis technique based on the principle of harmony in Javanese culture. The results of the study showed that the form of positive politeness acts that were most used by followers was by giving attention to the speech partners. Political propaganda power of dominant followers’ comments was in the form of the power to ask and support rather than the power of praise, the power of influence, the power of motivation, and the power of suggestion. It shows that Instagram account followers have an optimistic attitude towards Jokowi's leadership. Jokowi's managerial, and leadership performance has a positive face among followers. This power of praise, motivation, and advice is an essential component in the formation of children's character education in the current era of disruption of education.